Jaringan Islamisasi Gorontalo (Fenomena Keagamaan dan Perkembangan Islam di Gorontalo) - Mashadi Mashadi; Wahidah Suryani (Al-Ulum, 2018)
In this article, the authors argue that Gorontalo Municipality, which is believed to have been founded as the centre of government since 1728 AD, or precisely in 6 Sya'ban 1140 H., has become an "Islamic city". Sultan Amai, in 1525, is believed to be the first place to the cornerstone of Islam in this country. The king Matolodulakiki made Islam as the official religion of the kingdom during his reign by prioritizing the principle: “Adati hula-hulaa to saraa, saraa hula-hulaa to Qur’ani”. The king Eyato then refined the principle of Islamic and state fusion and adat since 1673. Furthermore, Sultan Botutihe emphasized the process of Islamization by moving the centre of government from Dungingi to a new location, which is currently the complex area of the Great Baiturrahim Mosque in Gorontalo municipality. This mosque is a historical landmark of the government and the centre of religion. Implicitly this means that the relationship between state, religion and adat has been so strong in Gorontalo. The principle of the spread of Islam at this time endures to a new development, namely "custom in Islam or Islam that is imposed". Furthermore, the network of Islamization in the 19th century until the present era mainly marked by the establishment of several organizations and institutions such as: Al-Huda, Al-Khairat, Muhammadiyah and NU.